Adaptation and Psychometrics of the Indonesian Version of Work and Meaning Inventory (WAMI) - Rahmi, Tuti; Fitriana, Efi; Harding, Diana; Agustiani, Hendriati (Opción, 2019)
Indonesia nowadays is incessantly encouraging the spirit of work. With the current ASEAN Economic Community (AEC), Indonesia must immediately step up to other countries by enhancing not only the performance but also the well-being of the employees. Meaningful work is one of the antecedents of per- formance and well-being. That is why it needs to be investigated in Indonesia. Thus, a valid and reliable meaningful work measurement tool is required to be used. A valid and reliable Work and Meaning Inventory (WAMI) is not yet available in Indonesian version and research on meaningful work has also not been conducted much in Indonesia. Thus, the development of WAMI valida- tion and adaptation is a noteworthy effort to be conducted. Objectives - The purpose of this research was to adapt and measure psychometric properties of the Indonesian version of WAMI. Method – A cross-sectional study was conducted. There were 193 respondents obtained from one local bank with a number of branches in Indonesia. Confirmatory factor analysis was tested to examine the scale. The convergent validity was examined by correlating WAMI with Utrecht Work Engagement Scale (UWES) and Job Satisfaction Survey (JSS). Discriminant validity was tested using Perceived Stress Scale (PSS), while reliability was assessed by using AVE and CR. Result – The con- firmatory factor analysis revealed the model of the WAMI that fitted the data best. The reliability of the scale was good. Work engagement and job satisfac- tion were positively associated with meaningful work; perceived stress was negatively associated with meaningful work.There were no differences across gender, but the differences appeared be- tween group ages and length of work. Conclusions – The finding of the study indicated that WAMI has satisfactory psychometric properties and provided supportive evidence for use in Indonesian context.